<span>x^2 - 9x + c
=x^2 - 2(x)(9/2) + (9/2)^2 is a perfect square
Therefore b = (9/2)^2 = 81/4
Ans: 81/4 </span>
Answer:
960
Step-by-step explanation:
You multiply all of the numbers together to get 960
As we can see that common difference is increasing to one more digit after every term
so it means
a21 = 231
Answer:
The correct answer is D) 7+(3+1)=(7+3)+1
Step-by-step explanation:
The associative property of addition states that it doesn't matter how you group numbers inside of parenthesis, it gives you the same answer. So even though the groupings are different in that example, the answer is still the same.
Answer:
(2x^2+7)
Step-by-step explanation:
5x^3 * 2x^2 = 10x^5
5x^3 * 7 = 35x^3